Influence of the substrate on the bulk properties of hybrid lead halide perovskite films. Issue 46 (11th November 2016) - Climent-Pascual, Esteban; Hames, Bruno Clasen; Moreno-Ramírez, Jorge S.; Álvarez, Angel Luis; Juarez-Perez, Emilio J.; Mas-Marza, Elena; Mora-Seró, Ivan; de Andrés, Alicia; Coya, Carmen
Abstract : Structure, morphology and concentration of defects in hybrid perovskites depend on the type of substrate used for film growth. Abstract : In addition to the known effect of the substrate on the interfacial properties of perovskite films, here we show that the bulk properties of hybrid lead halide perovskite films depend on the type of substrate used for film growth. Despite the relative large film thickness, ∼600 nm, the roughness and nature of the substrate layer (glass, FTO, TiO2 and PEDOT:PSS) affect not just the degree of preferential orientation and crystal grain size but also the lattice parameters of CH3 NH3 PbI3 films synthesized from the PbCl2 precursor. The obtained changes in lattice parameters indicate that the Pb–Pb distance varies by around 0.7%. We suggest that the substrate roughness and chemical nature determine the concentration of defects mainly by varying the chlorine content and probably by the incorporation of oxygen and iodine vacancies during film nucleation and growth. These differences also have consequences in the observed light induced transformations. Upon laser illumination, the formation of additional defects, most probably related to oxygen, is revealed by 110 and 165 cm −1 Raman peaks. With increasing laser power the chemical transformation into PbO x is clearly identified by the 140 and 275 cm −1 Raman peaks. The irreversible photoluminescence enhancement observed at low power with illumination time, also dependent on the substrate nature, is proposed to be due to the localization of the electron–hole excitons created in the vicinity of the light generated defects. These results shed light on the performance of the perovskite layer and help to understand how bulk processes, where ion migration is a conspicuous example, are severely affected by interfacial properties such as those imposed by the substrate.